Top caregiver concerns in Rett syndrome and related disorders: data from the US natural history study - Jeffrey L. Neul; Timothy A. Benke; Eric D. Marsh; Bernhard Suter; Lori Silveira; Cary Fu; Sarika U. Peters; Alan K. Percy; for the Rett syndrome Natural History Study Group (Journal of Neurodevelopmental Disorders, 2023)
Abstract Objective Recent advances in the understanding of neurodevelopmental disorders such as Rett syndrome (RTT) have enabled the discovery of novel therapeutic approaches that require formal clinical evaluation of efficacy. Clinical trial success depends on outcome measures that assess clinical features that are most impactful for affected individuals. To determine the top concerns in RTT and RTT-related disorders we asked caregivers to list the top caregiver concerns to guide the development and selection of appropriate clinical trial outcome measures for these disorders. Methods Caregivers of participants enrolled in the US Natural History Study of RTT and RTT-related disorders (n = 925) were asked to identify the top 3 concerning problems impacting the affected participant. We generated a weighted list of top caregiver concerns for each of the diagnostic categories and compared results between the disorders. Further, for classic RTT, caregiver concerns were analyzed by age, clinical severity, and common RTT-causing mutations in MECP2. Results The top caregiver concerns for classic RTT were effective communication, seizures, walking/balance issues, lack of hand use, and constipation. The frequency of the top caregiver concerns for classic RTT varied by age, clinical severity, and specific mutations, consistent with known variation in the frequency of clinical features across these domains. Caregivers of participants with increased seizure severity often ranked seizures as the first concern, whereas caregivers of participants without active seizures often ranked hand use or communication as the top concern. Comparison across disorders found commonalities in the top caregiver concerns between classic RTT, atypical RTT, MECP2 duplication syndrome, CDKL5 deficiency disorder, and FOXG1 syndrome; however, distinct differences in caregiver concerns between these disorders are consistent with the relative prevalence and impact of specific clinical features. Conclusion The top caregiver concerns for individuals with RTT and RTT-related disorders reflect the impact of the primary clinical symptoms of these disorders. This work is critical in the development of meaningful therapies, as optimal therapy should address these concerns. Further, outcome measures to be utilized in clinical trials should assess these clinical issues identified as most concerning by caregivers.